The interplay of homeostasis, inflammation, and oxidative stress in neurodegenerative disorders: the role of biological markers, antioxidants, lithium, and TMS — a proposed framework for preventing neurodegenerative disorders through biomarkers and multimodal therapies - Lado, Leonard; Misir, Aruna (Frontiers in Aging Neuroscience, 2026)
Neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) are among the most significant health challenges of aging, characterized by progressive cognitive and motor decline. Increasing evidence suggests that these conditions are not inevitable outcomes of aging but may instead be driven by preventable mechanisms involving oxidative stress, chronic inflammation, and disruptions in homeostasis. This manuscript proposes a preventive framework that integrates validated biomarkers: glial fibrillary acidic protein (GFAP), neurofilament light chain (NfL), soluble triggering receptor expressed on myeloid cells 2 (sTREM2), and YKL-40 or CHI3L1 by its more commonly used name: Chitinase-3-like protein 1 with multimodal therapeutic interventions, including antioxidants, lithium, and transcranial magnetic stimulation (TMS). Oxidative stress is positioned as a central mediator of neurodegeneration, with biomarkers serving as early indicators that enable detection before irreversible neuronal loss. This supports our proposal that NfL is not only a marker of pathology but also a measurable indicator of lithium’s effect in stabilizing axons and reducing neurodegeneration. These results align with our framework, which places TMS as a synergistic tool with lithium and antioxidants to modify both oxidative and neuroplastic pathways with a translational preventive strategy. Importantly, recent findings published in demonstrated that reducing dietary lithium by more than 50% in AD mouse models accelerated amyloid-β and tau pathology, increased microglial activation, and led to cognitive decline. Remarkably, lithium supplementation prevented these changes and preserved neuronal and cognitive function. These results provide powerful preclinical validation of our framework, reinforcing the concept that lithium deficiency may be pathogenic and that restoring physiological lithium levels could serve as a preventive therapy. The model also incorporates viral contributions (HSV-1, EBV) as triggers of chronic inflammation and amyloid pathology, providing a more comprehensive view of disease initiation. It further emphasizes the potential synergy of combining antioxidants with TMS, highlighting avenues for multimodal prevention. These findings reinforce the role of inflammation as both a driver and a modifiable factor in neurodegeneration. Our model integrates lithium’s anti-inflammatory effects with biomarker monitoring (e.g., YKL-40, sTREM2) to translate these insights into targeted preventive strategies. These results align with our framework, which places TMS as a synergistic tool with lithium and antioxidants to modify both oxidative and neuroplastic pathways, bridging state-of-the-art findings with a translational preventive strategy. We acknowledge limitations, including the need for improved biomarker specificity and sensitivity, inconsistent outcomes of antioxidant trials, the accessibility and cost of TMS, and the therapeutic window of lithium. Nonetheless, by reframing AD and PD as preventable rather than inevitable, our framework highlights a proactive approach that integrates molecular mechanisms, biomarkers, and multimodal therapies into a cohesive strategy with both scientific promise and translational potential.